What Motivates Students to Study Engineering? A Comparative Study between Males and Females in Saudi Arabia - Wafa Labib; Amal Abdelsattar; Yasser Ibrahim; Abdelhakim Abdelhadi (MDPI AG, 2021)
Motivation to study engineering in undergraduate study is of great importance to students. It encourages undergraduate students to enroll in an engineering program and continue their studies without dropping out. Male students enroll in engineering programs with large numbers compared to female students in many parts of the world. In Saudi Arabia, there were limited engineering programs for female students. In this research, the motivation to study engineering is studied and compared between male and female students in the College of Engineering at Prince Sultan University, the first private university in Saudi Arabia. The study was conducted through a detailed survey distributed to 41 male engineering management students and 45 female architectural engineering students. These students' performance and experience were considered and compared considering their gender to evaluate their persistence toward engineering study. According to the results obtained, the highest degree of the parents had a considerable effect on the selection of engineering major for male and female students. Most surveyed male and female students select an engineering major because of its positive impact on the community and its role in improving the way of life. Male students may differ in that they considered engineering in order to start their own business after graduation with a higher percentage compared to female students. There was a very limited role of the school in selecting engineering majors according to the surveyed male and female students. This role should be enhanced and utilized to encourage more female students to consider engineering majors in their college study.